Application of 7-azaisatins in enantioselective Morita–Baylis–Hillman reaction - He, Qing; Zhan, Gu; Du, Wei; Chen, Ying-Chun (Beilstein Journal of Organic Chemistry, 2016)
7-Azaisatin and 7-azaoxindole skeletons are valuable building blocks in diverse biologically active substances. Here 7-azaisatins turned out to be more efficient electrophiles than the analogous isatins in the enantioselective Morita–Baylis–Hillman (MBH) reactions with maleimides using a bifunctional tertiary amine, β-isocupreidine (β-ICD), as the catalyst. This route allows a convenient approach to access multifunctional 3-hydroxy-7-aza-2-oxindoles with high enantiopurity (up to 94% ee). Other types of activated alkenes, such as acrylates and acrolein, could also be efficiently utilized.
Keywords: 7-azaisatins; β-isocupreidine; bifunctional catalysis; maleimide; MBH reaction